Going China for study and pursue career in Africa - (:unkn) unknown (My University, 2016)
Based on interviews collected in Xi’an (People’s Republic of China), Brazzaville and Pointe-Noire (Congo), this article focuses on training and careers of African students graduated from Chinese universities. The increasing number of African students in Chinese universities is a phenomenon which occurs in a context of strengthened economic and political ties, but also gradual internationalization of Chinese universities that develop new curriculums in English.The survey shows that African graduates of Chinese universities are generally willing to work for a large Chinese company in Africa, but face many difficulties due to the poor recognition of their qualifications and the fact that the organization of Chinese companies operating abroad is not yet fully internationalized. Therefore, Chinese employers tend to confine them to translators or “cultural brokers jobs”.
Keywords: African Research